2016
DOI: 10.1007/s11136-016-1235-4
|View full text |Cite
|
Sign up to set email alerts
|

Translation, validity and reliability of the British Sign Language (BSL) version of the EQ-5D-5L

Abstract: PurposeTo translate the health questionnaire EuroQol EQ-5D-5L into British Sign Language (BSL), to test its reliability with the signing Deaf population of BSL users in the UK and to validate its psychometric properties.MethodsThe EQ-5D-5L BSL was developed following the international standard for translation required by EuroQol, with additional agreed features appropriate to a visual language. Data collection used an online platform to view the signed (BSL) version of the tests. The psychometric testing inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…We note that publishing without ND, appears to be a common practice in those Open Access articles cited in our review (e.g. Caporali et al 2016;Rogers et al 2016;Wrzosek et al 2016). Putting the translated instrument out in the public domain, such as a website, yields the same loss of control over usage even if the version is watermarked with ''do not copy'' (e.g.…”
Section: Item 6d Finalise and Archive A Reportmentioning
confidence: 83%
“…We note that publishing without ND, appears to be a common practice in those Open Access articles cited in our review (e.g. Caporali et al 2016;Rogers et al 2016;Wrzosek et al 2016). Putting the translated instrument out in the public domain, such as a website, yields the same loss of control over usage even if the version is watermarked with ''do not copy'' (e.g.…”
Section: Item 6d Finalise and Archive A Reportmentioning
confidence: 83%
“…experiencing a lack of motivation to socialise and meet people may be not as a result of feeling depressed, but rather be a response to many Deaf people’s normal experiences of social contexts where most of the hearing people within them are unable to communicate in BSL ([13] p117). This hypothesis is lent support in a validation study of the BSL version of EQ-5D-5 L (health questionnaire) [37], where a small number of Deaf people were interviewed to find out how they understood key terms contained within EQ-5D-5 L BSL. This revealed that everyday experiences of communication barriers could affect the conceptualisation of key terms e.g.…”
Section: Discussionmentioning
confidence: 89%
“…This analysis included participants' sociodemographic characteristics, but excluded the other health measures associated with the presence or absence of depression (p < 0.07; logistic regression, results reported in the Rogers et al study 130 ). The results indicate that those people who did not have depression had a higher utility value than those who did (coefficient 0.11, 95% CI 0.01 to 0.21; p = 0.029; n = 66).…”
Section: Eq-5d-5l Translation and Validation In Bsl (Study 4)mentioning
confidence: 99%
“…133 The EQ-5D-5L was translated into BSL and validated (see Chapter 6); this study concluded that it is a reliable measure of health status in the Deaf signing population in the UK. 130 The utility values used are reported in Chapter 6. The data from the translation and validation study were used to calculate EQ-5D utility values for the depression and remission health states included in the model.…”
Section: Utility Valuesmentioning
confidence: 99%